2005
DOI: 10.1097/00002508-200505000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pain-Related Factors Contributing to Muscle Inhibition in Patients With Chronic Low Back Pain

Abstract: When interpreting decreased muscle strength in terms of physical deconditioning in patients with chronic low back pain, submaximal performance has to be taken into account. The results suggest that patients with chronic low back pain who report increased psychologic distress and a higher level of current pain tend to show increased inhibition of muscle activity, leading to submaximal performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 35 publications
3
44
3
Order By: Relevance
“…Therefore, results can be influenced by several individual confounding factors such as motivation, pain tolerance, competitiveness (Mannion & Dolan, 1994); furthermore pain on exertion, anticipation or fear of pain and reflex inhibition of motor activation can be additional factors resulting in 152 inability or unwillingness to produce a truly maximal effort in patients with LBP (Menard et al, 1994;Vlaeyen et al, 1995;Crombez et al, 1996;Keller et al, 1999;Rashiq et al, 2003;Rainville et al, 2004;Al-Obaidi et al, 2005;Ropponen et al, 2005;Verbunt et al, 2005;Thomas et al, 2008;Huijnen et al, 2010). These individual factors might explain the absence or low correlations found in some studies between morphologic variables and performance (Parkkola et al, 1993;Gibbons et al, 1997a).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, results can be influenced by several individual confounding factors such as motivation, pain tolerance, competitiveness (Mannion & Dolan, 1994); furthermore pain on exertion, anticipation or fear of pain and reflex inhibition of motor activation can be additional factors resulting in 152 inability or unwillingness to produce a truly maximal effort in patients with LBP (Menard et al, 1994;Vlaeyen et al, 1995;Crombez et al, 1996;Keller et al, 1999;Rashiq et al, 2003;Rainville et al, 2004;Al-Obaidi et al, 2005;Ropponen et al, 2005;Verbunt et al, 2005;Thomas et al, 2008;Huijnen et al, 2010). These individual factors might explain the absence or low correlations found in some studies between morphologic variables and performance (Parkkola et al, 1993;Gibbons et al, 1997a).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…The force increment in response to this stimulus reflects the muscle force reserve or the difference between the maximum force that can be generated by the muscle and the maximum voluntary contraction force, in which nonphysiological factors play a role (Verbunt et al, 2003). This technique was used to compare healthy subjects with patients with LBP regarding knee extensor inhibition in a few studies (Suter & Lindsay, 2001;Verbunt et al, 2005); a lower central activation ratio was reported in patients experiencing increased psychological distress and with higher pain intensity (Verbunt et al, 2005).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Subjects performed a MVIC of the quadriceps with the knee locked at 90°flexion and the hip at 85°. Quadriceps MVIC torque values were normalized by body mass (Nm/kg) (Verbunt et al, 2005;Palmieri-Smith et al, 2010). Once the MVIC reached a plateau, an electrical stimulation was manually delivered to the quadriceps, via stimulating electrodes, to recruit any remaining muscle fibers (Snyder-Mackler et al, 1995) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…CAR ranges in healthy subjects were previously reported as 0.93-0.99 (Lewek et al, 2004) and 0.95-0.98 (Verbunt et al, 2005). Further, other studies have suggested 0.95 as a normal value of the CAR in healthy people, (Delitto, 1988;Hurley et al, 1992;Farquhar et al, 2005) although this has never been objectively examined.…”
Section: Introductionmentioning
confidence: 96%
“…However, along with its well-known physical benefits, exercise therapy can challenge maladaptive thoughts and beliefs and is associated with improvements regarding fear avoidance, pain catastrophizing, and self-efficacy in people with LBP. 22,[28][29][30][31][32][33][34] A better understanding of the psychological techniques used by physiotherapists to enhance uptake of exercise programmes could improve rehabilitation outcomes.…”
Section: Ré Sumémentioning
confidence: 99%